2018
DOI: 10.1097/01.reo.0000000000000123
|View full text |Cite
|
Sign up to set email alerts
|

Translating Research to Practice Using a Team-Based Approach to Cancer Rehabilitation: A Physical Therapy and Exercise-Based Cancer Rehabilitation Program Reduces Fatigue and Improves Aerobic Capacity

Abstract: Background and Objective: Intervention research has shown that exercise-based rehabilitation is safe and effective for reducing disease burden across the cancer continuum. However, the translation of this research to programs implemented in health care settings remains a challenge. This study describes the implementation of a physical therapy–based exercise program for patients who have been diagnosed with cancer and its effectiveness for reducing fatigue and improving aerobic capacity. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 29 publications
0
8
0
Order By: Relevance
“…has the potential to optimize patient care via improved decision making about the safest and most e cacious exercise referral to improve patients' long-term health, function, and quality of life across the cancer continuum. [21] American College of Sports Medicine guidelines for exercise testing and prescription [19] Cancer-speci c exercise risk screening tool [22] National Comprehension Cancer Network (NCCN): Survivorship Clinical Practice Guidelines V1.2020 (National Comprehensive Cancer Network, 2020) [23] Macmillan Cancer Rehabilitation pathways [24] Yes or No: New, worsening or di culty managing any of the following conditions: lymphedema, ostomy, signi cant weight uctuations, infection, ataxia, malnourishment, severe fatigue, bone/back/neck pain and unusual weakness Acvtiv Onco Model [20] Macmillan Cancer Rehabilitation pathways [24] High risk signs/symptoms Yes or No: presence of ≥1 complication or highrisk signs/symptoms associated with the following diseases: Cardiovascular or respiratory disease Previous stroke, neurological condition, or spinal cord injury…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…has the potential to optimize patient care via improved decision making about the safest and most e cacious exercise referral to improve patients' long-term health, function, and quality of life across the cancer continuum. [21] American College of Sports Medicine guidelines for exercise testing and prescription [19] Cancer-speci c exercise risk screening tool [22] National Comprehension Cancer Network (NCCN): Survivorship Clinical Practice Guidelines V1.2020 (National Comprehensive Cancer Network, 2020) [23] Macmillan Cancer Rehabilitation pathways [24] Yes or No: New, worsening or di culty managing any of the following conditions: lymphedema, ostomy, signi cant weight uctuations, infection, ataxia, malnourishment, severe fatigue, bone/back/neck pain and unusual weakness Acvtiv Onco Model [20] Macmillan Cancer Rehabilitation pathways [24] High risk signs/symptoms Yes or No: presence of ≥1 complication or highrisk signs/symptoms associated with the following diseases: Cardiovascular or respiratory disease Previous stroke, neurological condition, or spinal cord injury…”
Section: Discussionmentioning
confidence: 99%
“…Intervention is typically led by an exercise clinician with oversight from a rehabilitation or other clinical specialist including nursing. Although the effectiveness of these programs has not been reviewed exclusively, many studies have demonstrated positive effects and impacts for cancer survivors, including improved fatigue [21][22][23], function [21,22,24,25], quality of life [22], symptom management [25], tness [22], physical activity level [23], and health-care utilization [25].…”
Section: Clinically Supervised Exercise Servicesmentioning
confidence: 99%
See 1 more Smart Citation
“…has the potential to optimize patient care via improved decision making about the safest and most e cacious exercise referral to improve patients' long-term health, function, and quality of life across the cancer continuum. American College of Sports Medicine guidelines for exercise testing and prescription [19] Acvtiv Onco Model [20] Chronic [21] American College of Sports Medicine guidelines for exercise testing and prescription [19] Cancer-speci c exercise risk screening tool [22] National Comprehension Cancer Network (NCCN): Survivorship Clinical Practice Guidelines V1.2020 (National Comprehensive Cancer Network, 2020) [23] Macmillan Cancer Rehabilitation pathways [24] Yes or No: New, worsening or di culty managing any of the following conditions: lymphedema, ostomy, signi cant weight uctuations, infection, ataxia, malnourishment, severe fatigue, bone/back/neck pain and unusual weakness Acvtiv Onco Model [20] Macmillan Cancer Rehabilitation pathways [24] High risk signs/symptoms [21] National Comprehension Cancer Network (NCCN): Survivorship Clinical Practice Guidelines V1.2020 [23] Macmillan Cancer Rehabilitation pathways [24] Cancer-speci c exercise risk screening tool [22] Acvtiv Onco Model [20] [24] National Comprehension Cancer Network (NCCN): Survivorship Clinical Practice Guidelines V1.2020 [23] Focused review of safety considerations in cancer rehab [17] The [25] Exercise in Medicine in Oncology: ACSM 2019 Roundtable [2] Macmillan Cancer Rehabilitation pathways [24] Acvtiv Onco Model [20] Cancer-speci c exercise risk screening tool [22] Association of Clinical Oncology (ASCO) Management of Older Adults Guideline [26] The Interdisciplinary Rehabilitation Care Team and the Role of Physical Therapy in Survivor Exercise [6] International Society of Geriatric Oncology (SIOG) recommendations for management of cancer-related cognitive decline [27] Level 2 side effects Yes or No, presence of ≥1 of the following factors:…”
Section: Resultsmentioning
confidence: 99%
“…5 This evidence has formed the basis for many cancer rehabilitation programs that implement aerobic exercise training. 6,7 Although the efficacy of MICT for reducing CRF has been well established, the question remains whether other exercise modalities are as effective or potentially more effective. One of the modalities in question is high-intensity interval training (HIIT), which involves alternating intervals of high-intensity exercise and low-intensity exercise or rest.…”
mentioning
confidence: 99%